Comment on ‘Unexpected plasticity in the life cycle of Trypanosoma brucei’ - Keith R Matthews; Stephen Larcombe (eLife, 2022)
Schuster et al. make the important observation that small numbers of trypanosomes can infect tsetse flies, and further argue that this can occur whether the infecting parasites are developmentally ‘slender’ or ‘stumpy’(Schuster et al., 2021). We welcome their careful experiments but disagree that they require a rethink of the trypanosome life-cycle. Instead, the study reveals that stumpy forms are more likely to successfully infect flies, the key limit on parasite transmission, and we predict this advantage would be greatly amplified in tsetse infections in the field. Further, we argue that stumpy forms are defined by a suite of molecular adaptations for life-cycle progression, with morphology being a secondary feature. Finally, their dominance in chronic infections means most natural tsetse infections would involve stumpy forms, even in small numbers. Our interpretation does not require re-evaluation of the obligatory life cycle of the parasite, where stumpy forms are selected to sustain transmission.